A fuzzy overlay model for mapping adverse event risk in an active war theatre. Issue 5 (3rd September 2018) - Çakıt, Erman; Karwowski, Waldemar
ABSTRACT: This study discusses a series of fuzzy overlay analysis performed within a Geographic Information System (GIS) on recent adverse events throughout the war in Afghanistan. Three types of input variables are considered in terms of number of people killed, wounded and hijacked over the period 2004–2010 in order to identify the risk level in Afghanistan using fuzzy GIS approach. To conclude, most risky areas are accumulated in the eastern region of the country and major population centres. The proposed approach could enable military decision-makers to obtain a better understanding of the socio-spatial dynamic of incidents in Middle East.